Der Qubbet el-Hawa Nord-Friedhof (QHN) – Ein Elitefriedhof in Assuan: Erster Grabungsvorbericht (1.–3. Kampagne 2015–2019) - Kuhn, Robert (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2020)
During the unsecure situation in Aswan between 2011-2014, the local population of Aswan-Gharb found a so-far untouched and unknown necropolis containing mostly elite-tombs of the New Kingdom. After a short rescue season led by the local inspectorate in 2014, a cooperation between the Agyptisches Museum und Papyrussammlung Berlin and the local inspectorate of Aswan has been established. Since 2015, at least ten tombs have been detected and partly excavated. Eight are of New Kingdom date - mostly of the 18th.Dynasty - and at least one is of Old Kingdom/First Intermediate Period date.